Cambridge guide to American theatre (Cambridge, New York, 1992)
This book covers American theatre from its earliest history to the present, with spacial attention given to contemporary theatre throughout the United States. It provides some 2300 compact entries on people, venues, plays, and other theatrical phenomena, almost 100 topics in several major U.S. cities and such disparate subjects as Asian-American theatre, theatre architecture, female and male impersonation, magic, costume, Shakespear on the American stage, unions, Hispanic theatre, stage lighting, and dramatic theory. The entries, arraged alphabetically, provide information not only on mainstream topics but also on marginalized and alternative theatre, popular forms (such as the circus, vaudeville, and burlesque), and key plays from the U.S. thaetrical annals. The entries are also illuminated by 170 illustrations. A biographical index, a special feature of the book, lists dates and major occupations for more than 3000 individuals mentioned in the book
Keywords: theatre - united states - dictionaries